2008
DOI: 10.1016/j.visres.2008.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation changes directional sensitivity in a visual motion-sensitive neuron of the fly

Abstract: The blowfly visual system is a well-suited model to investigate the functional consequences of adaptation. Similar to cortical motion-sensitive neurons, fly tangential cells are directional selective and adapt during prolonged stimulation. Here we demonstrate in a tangential cell large changes in directionality after adaptation with motion in one direction. Surprisingly, depending on stimulation parameters, sensitivity for motion in the adapted direction relative to the unadapted direction can be either enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Within the expected coherences the lowest values were found after epinastine administration (Figures 7A,B, right). The low expected coherence after epinastine application indicates an increase in noise, which is likely to result from the overall decrease in spike rate (Kalb et al, 2008). However, comparing the mean coherence values with the expected coherences forming the respective upper bounds reveals significant drug effects, which cannot be attributed to an increase in noise alone.…”
Section: Resultsmentioning
confidence: 99%
“…Within the expected coherences the lowest values were found after epinastine administration (Figures 7A,B, right). The low expected coherence after epinastine application indicates an increase in noise, which is likely to result from the overall decrease in spike rate (Kalb et al, 2008). However, comparing the mean coherence values with the expected coherences forming the respective upper bounds reveals significant drug effects, which cannot be attributed to an increase in noise alone.…”
Section: Resultsmentioning
confidence: 99%
“…This window has been used in several previous publications (e.g., Harris et al, 2000; Kalb et al, 2008; Nordström et al, 2011), but some of the earliest effects of motion adaptation may not be visible this far into the response. For example, we showed that CDM has a clear effect on the initial response delay, only 30 ms after stimulus onset (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…During rest, the only type of motion that may carry physiologically relevant information is found in transient motion impulses. Signaling levels to prolonged visual motion are indeed reduced in immobilized animals (see e.g., Maddess and Laughlin, 1985; Clifford and Langley, 1996; Harris et al, 2000; Kurtz et al, 2000; Kalb et al, 2008), whereas transient pulses remain reliably encoded (Maddess and Laughlin, 1985; Kurtz et al, 2009a). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, to optimize the encoding of the fluctuations of environmental image features during the intersaccadic intervals, adaptation in the visual system should essentially take place on a timescale shorter than the duration of these intervals (i.e., within some tens of milliseconds) and may be driven by the high-frequency changes of the respective image parameters. Several physiological components of motion adaptation have been described at the different levels of the fly visual system (e.g., Maddess and Laughlin, 1985; Brenner et al, 2000a; Harris et al, 2000; Fairhall et al, 2001; Kurtz, 2007; Kalb et al, 2008; Liang et al, 2008). To what extent the time constants of these processes, which have been identified with experimenter designed motion stimuli, match the dynamics of parameter changes in the natural visual input, and how these adaptive processes are controlled, is still not clear.…”
Section: Processing Of Optic Flow In the Insect Nervous Systemmentioning
confidence: 99%